PERAN ECPAT (END CHILD PROSTITUTION, CHILD PORNOGRAPHY, AND TRAFFICKING OF CHILDREN FOR SEXUAL PURPOSES) DALAM MENANGANI KASUS PROSTITUSI ANAK DI MEKSIKO TAHUN 2005-2015 - Mutia Yirdam R; Den Yealta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Mexico is one of the leading hot spot for sexual exploitation of children. ECPAT as NGO which fights against sexual exploitation of children have some role in cases of child prostitution in Mexico. Based on the high level of child prostitution in Mexico and ECPAT have some role in that cases, the authors conducted a study to find out some role that ECPAT done for this child sexual exploiations case.This study use a constructivist perspective and international organizations theory. This study also includes the concept of human rights as the point of view of the theme of this study.The result of this research is ECPAT have been doing some cooperation with government and company in mexico as it’s effort to handle child prostitution cases.Keywords: ECPAT, Mexico, CSEC (Commercial Sexual Exploitations of Children), Child Prostitution